2022
DOI: 10.32479/ijeep.11945
|View full text |Cite
|
Sign up to set email alerts
|

Volatility Spillover between Stock Returns and Oil Prices during the Covid-19 Pandemic in ASEAN

Abstract: This study points to increase global monetary integration as a result of rising volatility spillovers. As a result, analyzing volatility spillovers for international areas that expand and improve through the usage of inventory returns and oil prices is critical. The EGARCH model is used to explore the Volatility Spillovers of oil agencies in five ASEAN international areas during the Covid-19 Pandemic. To assess the interrelationships of the ASEAN stock index as well as the path of volatility, data were acquire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Research interest on the impact of the coronavirus pandemic on both the broadly understood financial markets and the oil market has been strong over the last 2 years. Studies focused primarily on the impact of the pandemic on stock prices and stock indices (Al-Awadhi et al, 2020;Ali et al, 2020;Nadeem, 2022;Baig et al, 2021;Akbulaev et al, 2022;Alexandri et al, 2022) On the other hand, fewer studies analyzed the impact of COVID-19 on the commodity derivatives market, which is important from the perspective of companies bearing the risk of oil price changes. It is also worth emphasizing that with the rapid development of the commodity derivatives market, the relationships between the commodities market and other markets become more and more complex, thus constituting a significant source of risk that cannot be ignored in the economic system (Chen et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research interest on the impact of the coronavirus pandemic on both the broadly understood financial markets and the oil market has been strong over the last 2 years. Studies focused primarily on the impact of the pandemic on stock prices and stock indices (Al-Awadhi et al, 2020;Ali et al, 2020;Nadeem, 2022;Baig et al, 2021;Akbulaev et al, 2022;Alexandri et al, 2022) On the other hand, fewer studies analyzed the impact of COVID-19 on the commodity derivatives market, which is important from the perspective of companies bearing the risk of oil price changes. It is also worth emphasizing that with the rapid development of the commodity derivatives market, the relationships between the commodities market and other markets become more and more complex, thus constituting a significant source of risk that cannot be ignored in the economic system (Chen et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…EM is an associate accounting policy selcted by managers to win bound goals, personal interests, and company performance. It conjointly prevents managers from violating the contract defaults that can affect them and the organization (Murniati et al, 2019, Santos-Jaén et al, 2021, Redaputri et al, 2021, and Alexandri and Supriyanto, 2022.…”
Section: Emmentioning
confidence: 99%
“…Therefore, macro conditions or oil prices are related to the practices. The study by You et al (2018), Riduwan and Andajani (2019), Mela andPutra (2020), Supriyanto et al (2021a), Alexandri and Supriyanto (2022), Sugiyanto and Febrianti (2021), Shafie et al (2021), and Ye et al (2022) showed that Indonesian oil and fuel companies manage their revenues in an inverse connection.…”
Section: Introductionmentioning
confidence: 99%
“…Based on Jimenez et al (2021), the effect of the health index as a variable indicator of response shows that countries with good health conditions will have less impact on the fall in the stock price index during the health crisis caused by COVID-19. Components affecting the charge of return should be considered by financial experts and potential monetary experts (Alexandri & Supriyanto, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%